The combined action of ERG11 gene overexpression and its mutations in the development of Candida albicans resistance to triazolic antifungals - Yuri V. Nesvizhsky; Stanislav S. Afanasiev; Vitaly V. Zverev; Alexander D. Voropaev; Maxim S. Afanasiev; Elena A. Voropaeva; Elena V. Budanova; Ludmila M. Smirnova; Sofia A. Anisova; Yulia N. Urban (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. Modern medicine is faced with the resistance of Candida spp. to antimycotics, due to changes in the expression and structure of the ERG11 gene, the molecular target of triazoles. These mechanisms often operate simultaneously, but the interaction between them remains poorly understood.